Mapping Power and Interests: Stakeholder Dynamics in Sustainable Outdoor Recreation Governance in Pangandaran, Indonesia - Prawira, Mega Fitriani Adiwarna; Prawira, Aura Bulan Andhara (Journal of Tourism, Hospitality and Travel Management, 2024)
Outdoor recreation drives coastal tourism growth but often creates governance and environmental challenges, especially in ecologically sensitive areas like Pangandaran, West Java, Indonesia. This study examines the power and interest dynamics among stakeholders involved in Pangandaran’s outdoor recreation sector. Using a qualitative case study approach, data were collected through semi-structured interviews, document analysis, and stakeholder mapping. Eight stakeholder groups were identified, including government agencies, private tourism operators, industry associations, local communities, environmental organizations, tourists, media, and academic institutions. Findings reveal significant power imbalances, with government bodies, tourism businesses, and associations dominating decision-making, while local communities and environmental groups remain marginalized despite their high interest in sustainability. Key conflicts emerge around resource access, exclusion from governance, and trade-offs between economic expansion and ecological conservation. However, the study also identifies potential synergies, particularly through community-based tourism, eco-certification programs, and academic collaborations. The study emphasizes the need for inclusive governance models that strengthen community participation, integrate environmental safeguards, and balance stakeholder interests. Promoting collaborative platforms can enhance sustainability, equity, and resilience in Pangandaran’s tourism sector. This research contributes to stakeholder theory by applying power-interest mapping in tourism governance and provides actionable insights for developing sustainable coastal recreation strategies.